Implementing Authentic Materials to Improve Reading Comprehension - Octasary, Magvirah; Lakuana, Nurhaida; Mbau, Anitha Thalib (BABASAL English Education Journal, 2023)
The aim of this research is to measure the implementation of authentic materials in improving students’ reading comprehension of the eighth grade students at Madrasah Tsanawiyah Negeri Sausu. This research used quasi-experimental design.  It treated two classes namely experimental and control class. This quasi experimental research took 34 students of grade VIII B for the experimental class and 32 students of grade VIII A for the control. In choosing class to be a sample, this study used purposive sampling technique. This study used research instrument to collect data, namely questionnaire items and test. The result of data analysis indicate that the students’ mean score of the posttest is 66.9 in experimental class is higher than the mean score of the control class 52.5. It means that the students’ reading comprehension is improved because of  implementing the authentic materials since the mean score of pretest is significantly different from the mean score of posttest. In conclusion, the implementation of Authentic Materials can improve students’ reading comprehension.